Insight into biomass upgrade: A review on hydrogenation of 5-hydroxymethylfurfural (HMF) to 2,5-dimethylfuran (DMF) - Endot, N. A.; Junid, R.; Jamil, M. S. S. (MDPI, 2021)
Recent developments in the transformation of biobased 5-hydroxymethylfurfural (HMF) into a potential liquid fuel, 2,5-dimethylfuran (DMF), are summarised. This review focuses briefly on the history of HMF conversion to DMF in terms of the feedstock used and emphasises the ideal requirements in terms of the catalytic properties needed in HMF transformation into DMF. The recent state of the art and works on HMF transformation into DMF are discussed in comparison to noble metals and non-noble metals as well as bimetallic catalysts. The effect of the support used and the reaction conditions are also discussed. The recommendations for future work and challenges faced are specified.